Optimasi kinerja proses distilasi minyak akar wangi dengan modifikasi suhu dan kesetimbangan fasa - Meika Syahbana Rusli; Erliza Noor; . Risfaheri; Edi Mulyon; Tuti Tutuarim; Rosniyati Suwarda (Institut Pertanian Bogor, 2009)
This research aims was to improve distillation process performance of vetiver oil in term of oil recovery and quality and energy efficiency through optimizing process condition. The main approach used in this work is stepwise increased steam pressure and flow rate along the distillation process. This method combined the relationship between temperature, phase equilibrium and boiling point of chemical constituents of vetiver oil. Distillation process with increased pressure was observed improve the oil recovery. while the oil quality was maintained. The energy efficiency was also improved through reduced distillation time. Increased steam flow rate significantly affect total oil recovery. The steam flow rate of 2 1/hr/kg material result in an vetiver oil recovery of 90 percent.